Comparative genomic profiling of glandular bladder tumours - Maurer, Angela; Ortiz-Bruechle, Nadina; Guricova, Karolina; Rose, Michael; Morsch, Ronja; Garczyk, Stefan; Stöhr, Robert; Bertz, Simone; Golz, Reinhard; Reis, Henning; Bremmer, Felix; Zimpfer, Annette; et al. (Virchows Archiv, 2020)
Primary glandular bladder tumours (bladder adenocarcinoma [BAC], urachal adenocarcinoma [UAC], urothelial carcinoma with glandular differentiation [UCg]) are rare malignancies with histological resemblance to colorectal adenocarcinoma (CORAD) in the majority of this subgroup. Definite case numbers are very low, molecular data are limited and the pathogenesis remains poorly understood. Therefore, this study was designed to complement current knowledge by in depth analysis of BAC (n = 12), UAC (n = 13), UCg (n = 11) and non-invasive glandular lesions (n = 19). In BAC, in addition to known alterations in TP53, Wnt, MAP kinase and MTOR pathway, mutations in SMAD4, ARID1A and BRAF were identified. Compared to published data on muscle invasive bladder cancer (BLCA) and CORAD, UCg exhibited frequent "urothelial" like alterations while BAC and UAC were characterised by a more "colorectal" like mutational pattern. Immunohistochemically, there was no evidence of DNA mismatch repair deficiency or PD-L1 tumour cell positivity in any sample. Depending on the used antibody 0-45% of BAC, 0-30% of UCg and 0% UAC cases exhibited PD-L1 expressing tumour associated immune cells. A single BAC (9%, 1/11) showed evidence of ARID1A protein loss, and two cases of UCg (20%, 2/10) showed loss of SMARCA1 and PBRM1, respectively. Taken together, our data suggest at least in part involvement of similar pathways driving tumourigenesis of adenocarcinomas like BAC, UAC and CORAD independent of their tissue origin. Alterations of TERT and FBXW7 in single cases of intestinal metaplasia further point towards a possible precancerous character in line with previous reports.
CRIS-Team WoS Importer:2020-04-07